The effect of high-dose intramuscular epinephrine on the recovery of spontaneous circulation in an asphyxia‐induced cardiac arrest rat model - Daesung Lim; Soo Hoon Lee; Dong Hoon Kim; Changwoo Kang; Jin Hee Jeong; Sang Bong Lee (BMC Cardiovascular Disorders, 2021)
Abstract Background Obtaining vascular access can be challenging during resuscitation following cardiac arrest, and it is particularly difficult and time-consuming in paediatric patients. We aimed to compare the efficacy of high-dose intramuscular (IM) versus intravascular (IV) epinephrine administration with regard to the return of spontaneous circulation (ROSC) in an asphyxia-induced cardiac arrest rat model. Methods Forty-five male Sprague-Dawley rats were used for these experiments. Cardiac arrest was induced by asphyxia, and defined as a decline in mean arterial pressure (MAP) to 20 mmHg. After asphyxia-induced cardiac arrest, the rats were randomly allocated into one of 3 groups (control saline group, IV epinephrine group, and IM epinephrine group). After 540 s of cardiac arrest, cardiopulmonary resuscitation was performed, and IV saline (0.01 cc/kg), IV (0.01 mg/kg, 1:100,000) epinephrine or IM (0.05 mg/kg, 1:100,000) epinephrine was administered. ROSC was defined as the achievement of an MAP above 40 mmHg for more than 1 minute. Rates of ROSC, haemodynamics, and arterial blood gas analysis were serially observed. Results The ROSC rate (61.5%) of the IM epinephrine group was less than that in the IV epinephrine group (100%) but was higher than that of the control saline group (15.4%) (log-rank test). There were no differences in MAP between the two groups, but HR in the IM epinephrine group (beta coefficient = 1.02) decreased to a lesser extent than that in the IV epinephrine group with time. Conclusions IM epinephrine induced better ROSC rates compared to the control saline group in asphyxia-induced cardiac arrest, but not compared to IV epinephrine. The IM route of epinephrine administration may be a promising option in an asphyxia-induced cardiac arrest.